CD147 Mediates 5-Fluorouracil Resistance in Colorectal Cancer by Reprogramming Glycolipid Metabolism - Dong, Shuohui; Li, Songhan; Wang, Xiaoyan; Liang, Shuo; Zhang, Wenjie; Li, Linchuan; Xu, Qian; Shi, Bowen; Cheng, Zhiqiang; Zhang, Xiang; Zhong, Mingwei; Zhang, Guangyong; et al. (Frontiers in Oncology, 2022)
Chemoresistance against 5-fluorouracil (5-FU) is a major issue for colorectal cancer (CRC) patients. Increasing evidence for the roles of CD147 in glycolipid metabolic reprogramming and chemoresistance of tumor cells has emerged in recent years. However, whether CD147 contributes to 5-FU resistance in CRC and the role of abnormal glycolipid metabolism in this process remain poorly understood. We analyzed CD147 expression in primary tumor samples of CRC patients and found that upregulated CD147 correlated with decreased 5-FU chemosensitivity and an unfavorable prognosis of CRC patients. Moreover, in vivo and in vitro experiments confirmed that CD147 regulates glycolipid metabolism through two separate pathways. Mechanistically, CD147 upregulates HIF-1α-mediated glycolysis by activating the PI3K/AKT/mTOR pathway and CD147 also attenuates PPARα-mediated fatty acid oxidation by activation of the MAPK pathway. Most importantly, we found that CD147 confers 5-FU resistance in CRC via these glycolipid metabolic signatures. Our results demonstrated that CD147 is a potential 5-FU resistance biomarker for CRC patients and a candidate therapeutic target to restore 5-FU sensitivity of 5-FU-resistant CRC by remodeling glycolipid metabolism.